Trophy constrains the temperature effect on ciliate species turnover rates - J. L. S. Hansen; A. Altenburger; L. Haraguchi; J. Carstensen; H. H. Jakobsen (Ecosphere)
Abstract We applied FlowCam analysis cross‐validated by 18S rDNA sequences and taxonomic literature to study seasonal and short‐term population dynamics and species turnover in ciliate plankton during 15 months with high‐frequency samplings in a shallow temperate estuary in Denmark. FlowCam imagery identified 27 phenotypic ciliate entities, and 8 genotypes were identified. The analyses showed strong seasonality in biomass, abundance, diversity, trophy, and species turnover. The abundance of mixotrophic ciliates increased 30‐fold from winter to summer, whereas that of heterotrophic ciliates increased only five times. The two trophic groups also displayed contrasting seasonal diversity patterns. Heterotrophic ciliates increased in richness from 5.5 species in winter to 10.5 species in summer in 10 mL, whereas species richness of the mixotrophic community, dominated by Mesodinium rubrum, remained relatively constant with three species per 10 mL sample. Daily species turnover calculated from the decay of similarity was highest for heterotrophic ciliates, and community change rates of 3.1, 15.8, and 30.6% day−1 were significantly related to ambient temperatures of 4.8, 8.4, and 16°C, respectively. Oscillating species‐specific growth rates due to prey–predator interactions can explain faster species turnover rates in heterotrophic ciliates. By contrast, the mixotrophic ciliate community harvests a common supplementary energy source, which may dampen their species‐specific population oscillations.